TOGMOL LEADERSHIP, AGILITY, AND ADAPTABILITY OF PUBLIC SERVICES AMIDST PANDEMIC - Listyaningsih Listyaningsih (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This research aims to describe how local governments develop agility and adaptability in the midst of a pandemic and the various problems and limitations they face, to maintain the performance of their public services through evaluation of public services which is relevant with local characteristics. The study was conducted in Lebak Regency, Banten Province, a district that represents a rural area with relatively limited financial capacity, accessibility conditions, and infrastructure. Data was collected through participant observation, in-depth interviews, and documentation study; and analyzed qualitatively. The results of the study show that adaptation and agility can be realized innovatively, even though it is faced with various problems and limitations. Political leadership and bureaucracy that are “togmol” in organizing and mobilizing the bureaucracy are the determining factors for the success of its implementation. The results of this study contribute to the disciplinary area of public services and governance, and can practically be used to encourage public service providers in Indonesia, in particular, to increase adaptability and agility in the midst of a situation that changes rapidly and is full of uncertainty, even with various obstacles and limitations.